SiPinjam as an Information System for Lending Goods in the Department of Information Technology and Computers - Dodi Sopandi; Muhammad Izzudin A (Yayasan Insan Mulia Bima, 2024)
The information system for lending goods in the Department of Information and Computer Technology is designed to help the document writing process that is still done manually. In the era of digitalization in the current time, it is possible to keep up with all kinds of changes in the times, especially in the field of technology. Therefore, the development of this Lending Information System aims to make all forms of manual recording into digital. The final result of this research is the creation of a web-based lending system that can make it easier for staff to manage inventory of goods in the Department of Information and Communication Technology to enhance performance. ABSTRAK Sistem Informasi peminjaman barang di Jurusan Teknologi Informasi dan Komputer dirancang untuk membantu penulisan dokumen yang masih dilakukan secara manual. Di era digitalisasi pada zaman sekarang memungkinkan untuk mengikuti segala bentuk perubahan zaman khususnya dalam dunia teknologi. Karena itu pengembangan Sistem Informasi Peminjaman barang ini bertujuan untuk memudahkan segala bentuk pencatatan secara manual menjadi digital. Hasil akhir dari penelitian ini adalah terciptanya suatu sistem peminjaman berbasis web yang dapat memudahkan staff dalam pengelolaan inventory barang di jurusan Teknologi Informasi dan Komunikasi untuk meningkatkan kinerja.